ARTIFICIAL INTELLIGENCE TECHNOLOGIES AS A TOOL FOR ADVANCING ENGLISH SPEAKING SKILLS IN UZBEK EDUCATIONAL SETTINGS - EGAMOVA, Munisa (The Lingua Spectrum, 2025)
This article examines the use of artificial intelligence (AI) technologies in improving English speaking skills in Uzbekistan. As the demand for oral skills grows, AI-based tools, including mobile pronunciation applications, chatbots, and automated feedback systems, are increasingly being integrated into the learning process. The study highlights the advantages of artificial intelligence in language education, its current applications, challenges, and future opportunities. It also includes perspectives from international and local scholars to provide a broader scientific view.